2021
DOI: 10.1002/edn3.244
|View full text |Cite
|
Sign up to set email alerts
|

Land use and season drive changes in soil microbial communities and related functions in agricultural soils

Abstract: Soil microorganisms are important for the maintenance of soil health and related functions. Agricultural management practices such as land use, season, and fertilizer affect soil microbial community structures. However, the effect of these management practices on soil microorganisms and related functions, influenced by regionally different soil types, is still not clear. Hence, the study was conducted in an Andosol (volcanic soil) dominated agricultural region in a cool temperate climate to determine the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…The significant difference in bacterial community structure between MC and EXT_DP seen at sampling event 1 did persist into sampling event 2, but not into the four subsequent sampling events. This would suggest that in this specific instance, the tillage event which occurred (after sampling event 1 and before sampling event 2) did impact the seasonal stability of this pairwise difference, as such events have been reported to do ( Madegwa and Uchida, 2021 ). This was however the only pairwise difference, in either fungal or bacterial community structure, to be affected in this way.…”
Section: Discussionmentioning
confidence: 62%
“…The significant difference in bacterial community structure between MC and EXT_DP seen at sampling event 1 did persist into sampling event 2, but not into the four subsequent sampling events. This would suggest that in this specific instance, the tillage event which occurred (after sampling event 1 and before sampling event 2) did impact the seasonal stability of this pairwise difference, as such events have been reported to do ( Madegwa and Uchida, 2021 ). This was however the only pairwise difference, in either fungal or bacterial community structure, to be affected in this way.…”
Section: Discussionmentioning
confidence: 62%
“…Environmental variation across seasons is a different kind of perturbation for microbial communities, and it has been shown that seasonality influences microbial communities of soil [ 73 75 ], water [ 76 , 77 ] and host-associated microbiomes [ 78 , 79 ]. We found that skin bacterial communities of A. altamirani vary across seasons, particularly in pre-metamorphic axolotls which have a lower bacterial diversity compared to metamorphic axolotls.…”
Section: Discussionmentioning
confidence: 99%
“…One of the drawbacks of these approaches targeting delivery of microbes to a new environment is maintaining the stability of these introduced microbes over time, as the microbes will have to compete for resources (nutrients, space) with a background microbiome in the new environment. An alternative to delivering microbes to a new environment is to make local changes in the soil conditions (in situ changes) through agricultural practices as a way to alter the soil's microbial composition and achieve disease control (Hermans et al, 2020; Madegwa & Uchida, 2021). For instance, the use of seasonal cover crops has been linked with changes in the soil microbiome (Kim et al, 2020) and in some cases with disease suppression (Wright et al, 2017).…”
Section: Introductionmentioning
confidence: 99%